Endothelial actin depolymerization mediates NADPH oxidase-superoxide production during flow reversal - Choy, Jenny S. (American Physiological Society, 2013)
Slow moving blood flow and changes in flow direction, e.g., negative wall shear stress, can cause increased superoxide (O(2)(·−)) production in vascular endothelial cells. The mechanism by which shear stress increases O(2)(·−) production, however, is not well established. We tested the hypothesis that actin depolymerization, which occurs during flow reversal, mediates O(2)(·−) production in vascular endothelial cells via NADPH oxidase, and more specifically, the subunit p47(phox). Using a swine model, we created complete blood flow reversal in one carotid artery, while the contralateral vessel maintained forward blood flow as control. We measured actin depolymerization, NADPH oxidase activity, and reactive oxygen species (ROS) production in the presence of various inhibitors. Flow reversal was found to induce actin depolymerization and a 3.9 ± 1.0-fold increase in ROS production as compared with forward flow. NADPH oxidase activity was 1.4 ± 0.2 times higher in vessel segments subjected to reversed blood flow when measured by a direct enzyme assay. The NADPH oxidase subunits gp91(phox) (Nox2) and p47(phox) content in the vessels remained unchanged after 4 h of flow reversal. In contrast, p47(phox) phosphorylation was increased in vessels with reversed flow. The response caused by reversed flow was reduced by in vivo treatment with jasplakinolide, an actin stabilizer (only a 1.7 ± 0.3-fold increase). Apocynin (an antioxidant) prevented reversed flow-induced ROS production when the animals were treated in vivo. Cytochalasin D mimicked actin depolymerization in vitro and caused a 5.2 ± 3.0-fold increase in ROS production. These findings suggest that actin filaments play an important role in negative shear stress-induced ROS production by potentiating NADPH oxidase activity, and more specifically, the p47(phox) subunit in vascular endothelium.